2018
DOI: 10.1038/s41419-018-1015-x
|View full text |Cite
|
Sign up to set email alerts
|

VDAC2 interacts with PFKP to regulate glucose metabolism and phenotypic reprogramming of glioma stem cells

Abstract: Plastic phenotype convention between glioma stem cells (GSCs) and non-stem tumor cells (NSTCs) significantly fuels glioblastoma heterogeneity that causes therapeutic failure. Recent progressions indicate that glucose metabolic reprogramming could drive cell fates. However, the metabolic pattern of GSCs and NSTCs and its association with tumor cell phenotypes remain largely unknown. Here we found that GSCs were more glycolytic than NSTCs, and voltage-dependent anion channel 2 (VDAC2), a mitochondrial membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 69 publications
0
47
1
Order By: Relevance
“…It induces mitochondrial dysfunction, release of ROS and ultimately promotes ferroptosis by directly binding to VDAC2 7 . High expression of VDAC2 was associated with a longer OS and negatively correlated with glioma grades 26 . DNAJB6 is an HSP40 family protein that has significant influence on the inhibition of tumour growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It induces mitochondrial dysfunction, release of ROS and ultimately promotes ferroptosis by directly binding to VDAC2 7 . High expression of VDAC2 was associated with a longer OS and negatively correlated with glioma grades 26 . DNAJB6 is an HSP40 family protein that has significant influence on the inhibition of tumour growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…At variance with this notion, CSCs show a unique metabolic adaptation that is determined by the surrounding environment, such as the hypoxic niche of solid tumors, regions with adequate levels of oxygen (normoxia), active growing regions of the tumor and metastatic sites [94, 95, 99101]. In a few instances, this wide adaptation has generated controversial results: Vlashi et al [102] showed that glioma CSCs relied mainly on OXPHOS for energy supply, while other studies described that glioma CSCs are driven by a glycolytic reprogramming, exhibiting more fragmented mitochondria than neuronal stem cells and downregulation of mitochondrial respiratory activity in GSCs [103]. Although CSCs denote an elevated degree of metabolic plasticity, growing evidence suggests that these cells rely more on OXPHOS for energy production, with this being a far more efficient process in ATP generation than glycolysis (as recently reviewed in refs.…”
Section: Mitophagy In Cscs: a Role In Metabolic Reprogrammingmentioning
confidence: 99%
“…Therefore, the findings at CSCs after compound 1 treatment of MDA-MB-231 cells, increased GM3, IV 6 Neu5Ac-nLc 4 Cer, GalNAc-GM1b, Gb 4 Cer, and GM2, could indicate CSC glycolysis slowdown. Cancer stem cells of glioma are more glycolytic than non-CSCs due to a mitochondrial voltage-dependent anion channel that controls the phenotype transition between glioma stem cells and non-stem cells 31 . The channel is highly expressed in non-CSC relative to CSC and coupled to a glycolytic rate-limiting enzyme platelet-type of phosphofructokinase on mitochondrion to inhibit kinase-mediated glycolysis required for CSC maintenance.…”
Section: Discussionmentioning
confidence: 99%